Legal Controls for the Process of the Lawsuit in the International Court of Justice - Ghadbane, Somia (Journal of Legal Studies and Researches, 2023)
The texts of the Statute of the Court set the objective rules for convening the Court’s jurisdiction and the most important modalities that are commensurate with the requirements of international law. The most important procedural rules through which the disputing countries can file a case before the court, whether it comes to written or oral procedures, to ensure the judicial work of the court.